Recent Progress of Rechargeable Batteries Using Mild Aqueous Electrolytes. Issue 1 (19th September 2018) - Huang, Jianhang; Guo, Zhaowei; Ma, Yuanyuan; Bin, Duan; Wang, Yonggang; Xia, Yongyao
Abstract: Given the low cost, ease of fabrication, high safety, and environmental‐friendly characteristics, aqueous rechargeable batteries using mild aqueous solutions as electrolytes (pH is close to 7) and a monovalent/multivalent metal ion as charge carrier, are attracting extensive attention for energy storage. However, accompanied by advantages of mild aqueous electrolyte mentioned above, there are some challenges that stand in the way of the development of these aqueous rechargeable batteries, such as the narrow stable electrochemical window of water, instability of electrode materials, undesired side reactions, etc. In recent years, a massive effort is devoted to overcoming the drawbacks, and some encouraging works have arisen. In this review, the latest advances of electrolyte and electrode materials in aqueous batteries based on monovalent ion (Li +, Na +, K + ) and multivalent ion (Zn 2+, Mg 2+, Ca 2+, Al 3+ ) are briefly reviewed. Abstract : Rechargeable batteries using mild aqueous electrolytes (pH is close to 7) provide a promising solution for the large‐scale energy storage and wearable/biocompatible applications due to the high safety and low cost. Three development tendencies of these batteries are summarized: charge carriers from monovalent ions to multivalent ions; electrolyte composition from "salt‐in‐water" to "water‐in‐salt"; electrodes from inorganic materials to organic materials.